Mesh fixation technique for inguinal hernia repair: protocol for an umbrella review with integrated and updated network meta-analysis - Techapongsatorn, Suphakarn (BMJ Open, 2019)
INTRODUCTION: Inguinal hernia mesh repair is the standard care for symptomatic inguinal hernia. Mesh fixation is used to keep mesh in place for which various mesh fixation techniques have been used in open and laparoscopic inguinal hernia repair, but their effectiveness has remained inconclusive. Therefore, we developed a protocol for an umbrella review in order to summarise the evidences with integrate and update data of different mesh fixation techniques in both open and laparoscopic inguinal hernia repair. METHODS AND ANALYSIS: Previous systematic reviews and meta-analyses will be identified from Medline, Scopus, Cochrane Databases, EMBASE, Database of Abstracts of Reviews of Effects, PROSPERO Register, CINAHL, JBISRIS, EPPI-Centre, Wiley Online Library and Science Direct database. Two reviewers will independently determine studies for eligibility. Disagreement will be solved by consensus and arbitrated by the third reviewer. Data extraction will also be performed by two independent reviewers. For umbrella review, a descriptive analysis will be applied to describe evidence of mesh fixation effectiveness. Overlapping studies and excess significance test will be performed to assess whether previous evidences are bias. In addition, individual studies from meta-analysis and additional published studies will be pooled using network meta-analyses. We will use I(2) statistic and Cochran’s Q test to assess heterogeneity. Risk of bias and publication bias, if appropriate, will be evaluated, as well as overall strength of the evidence. ETHICS AND DISSEMINATION: This protocol has been registered with PROSPERO and approved with Institutional Review Board, Faculty of Medicine Vajira Hospital, Navamindradhiraj University, Bangkok, Thailand (COA 167/2018). The results will be published in peer-reviewed journal. PROSPERO REGISTRATION NUMBER: CRD42018111773